Our journey to new places using different spaces: A teaching degree totally online - O'Hare, Sheena; Pelliccione, Lina; Kuzich, Sonja (The University of Auckland, Auckland University of Technology, and Australasian Society for Computers in Learning in Tertiary Education, 2009)
The investment in technology to support delivery through Open University Australia (OUA) is a significant step in opening up the potential to increase efficiencies in service delivery to remote locations and indeed the world - as well as to develop new course offerings that do not add to the strain on ‘physical’ resources. Whilst Curtin University is currently the ‘only player’ in the Bachelor of Education Primary Education OUA arena it is wise to consolidate its leading position by understanding the distinct and real trends of student attraction and retention to enhance its status, position and ultimate economic viability in this sphere. This paper reports on a pilot study conducted to determine the student attrition rates in the very first offering of four OUA units in study period one. The results of the pilot study have informed the design of a much larger research project which aims to profile the students participating in the OUA Bachelor of Education Primary course in order to develop a greater understanding of those factors that impact on attrition rates thus informing future practice